Expression of oxysterol pathway genes in oestrogen‐positive breast carcinomas. (24th April 2017) - Kloudova, Alzbeta; Brynychova, Veronika; Vaclavikova, Radka; Vrana, David; Gatek, Jiri; Mrhalova, Marcela; Kodet, Roman; Soucek, Pavel
Summary: Objective: This study investigated whether gene expression levels of key modulators of the oxysterol signalling pathway modify the prognosis of patients with oestrogen receptor‐positive (ER+) breast carcinomas via interaction with endocrine therapy. Context: The prognosis of patients with ER+ breast carcinoma depends on several factors. Previous studies have suggested that some oxygenated forms of cholesterol (oxysterols) bind to oestrogen receptor and anti‐oestrogen binding site which may deregulate cholesterol homoeostasis and influence effect of therapy. Design: The expression levels of 70 oxysterol pathway genes were evaluated in a test set of breast carcinomas differing in ER expression. The genes differentially expressed in ER+ tumours were assessed in a comprehensive set of ER+ tumours to evaluate their clinical significance. Patients: A total of 193 primary patients with breast carcinoma were included. Measurements: The transcript levels were determined by quantitative real‐time polymerase chain reaction. Results: The expression levels of 23 genes were found to be specifically dysregulated in ER+ tumours compared to ER− tumours of the test set. The expression levels of ABCG2, CYP7B1, CYP24A1, CYP39A1 and CH25H genes were found to be strongly associated with disease stage; however, none of the gene expression levels were associated with disease‐free survival in patients treated with endocrine therapy. Conclusions: The expression of a number of oxysterol pathway genes is significantly modulated by ER expression and associated with the clinical stage of patients. However, the expression of oxysterol pathway genes was not found to modify the prognosis of ER+ patients with breast carcinoma treated with endocrine therapy.